2015
DOI: 10.1007/s11517-015-1311-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive classification of self-paced upper-limb analytical movements with EEG

Abstract: The extent to which the electroencephalographic activity allows the characterization of movements with the upper limb is an open question. This paper describes the design and validation of a classifier of upper-limb analytical movements based on electroencephalographic activity extracted from intervals preceding self-initiated movement tasks. Features selected for the classification are subject specific and associated with the movement tasks. Further tests are performed to reject the hypothesis that other info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…individual finger movements [4], types of wrist movement [14,41,42], analytical upper limb movements [16], and variation in speed and force of foot movements [13,21]. However, the performance was better compared to the findings in a recent study where force and speed were decoded from the MRCP associated with palmar grasps using a single electrode and a single Laplacian-filtered channel [20] suggesting that several electrodes are needed to obtain high classification accuracy.…”
Section: Movement Discriminationmentioning
confidence: 84%
“…individual finger movements [4], types of wrist movement [14,41,42], analytical upper limb movements [16], and variation in speed and force of foot movements [13,21]. However, the performance was better compared to the findings in a recent study where force and speed were decoded from the MRCP associated with palmar grasps using a single electrode and a single Laplacian-filtered channel [20] suggesting that several electrodes are needed to obtain high classification accuracy.…”
Section: Movement Discriminationmentioning
confidence: 84%
“…In the here presented work we report the performance of a BCI using 1 s time windows and 19 EEG electrodes and it has been already shown that the accuracy of classifier increases using longer time window after onset [38] and denser EEG electrodes around the motor cortex [33]. Adding more features such as movement related cortical potential (MRCP) to the proposed system may further improve the performance [30,32].…”
Section: Discussionmentioning
confidence: 89%
“…flexion versus extension or pronation versus supination) were decoded with average accuracy ranging from 60 to 80% [36]. A few other groups have reported some preliminary work on multi-class decoding using motor imagery and execution of movements from the same upper limb [33,37,38]. Yong et al have shown a 3-class BCI system that discriminates EEG signals corresponding to rest, imaginary grasp, and elbow movement [33].…”
Section: Introductionmentioning
confidence: 99%
“…(4) El uso del robot de rehabilitación y el sistema sensorial adjunto para la valoración del progreso en el proceso de rehabilitación y asistencia, mediante variables biomecánicas (de los , mediante variables bioeléctricas periféricas tales como EMG de las que extraer fenómenos tales como la fatiga muscular asociada al uso de la tecnología o aspectos relacionados con la coordinación muscular Barroso et al, 2016), y mediante variables bioeléctricas centrales, tales como EEG, (Ibáñez et al, 2015).…”
Section: Robótica De Rehabilitación Y Asistenciaunclassified